Creative Economic Development Through Weaving Umkm As An Effort To Increase Community Income In Sangiang Village, Wera District - Nurhalifah; Ihwan P. Syamsudin; Rafiuudin (JURNAL ECONOMINA, 2026)
The development of a creative economy based on Micro, Small, and Medium Enterprises (MSMEs) weaving in Sangiang Village, Wera District, plays a strategic role in increasing local community income. However, the problems faced lie in suboptimal business management, limited product innovation, and weak marketing access, which impacts the low competitiveness of woven products. This study aims to examine in-depth efforts to develop a creative economy through MSMEs weaving as a strategy to increase community income. The research method used is qualitative with a descriptive approach, through data collection techniques such as observation, interviews with MSMEs and the community, and documentation. Data analysis was carried out systematically through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the development of the creative economy through MSMEs weaving has been ongoing, but is not yet optimal and sustainable. The main weaknesses lie in aspects of design innovation, the use of digital marketing technology, and increasing human resource capacity. Therefore, the necessary strategies include strengthening product creativity based on local wisdom, improving business actors' skills, expanding marketing networks, and government support in the form of training and facilitating market access. In conclusion, the development of the creative economy through targeted and sustainable weaving MSMEs can increase community income while strengthening the local cultural identity of Sangiang Village.